Global consensus recommendations on menopause in the workplace: A European Menopause and Andropause Society (EMAS) position statement. (September 2021) - Rees, Margaret; Bitzer, Johannes; Cano, Antonio; Ceausu, Iuliana; Chedraui, Peter; Durmusoglu, Fatih; Erkkola, Risto; Geukes, Marije; Godfrey, Alan; Goulis, Dimitrios G.; Griffiths, Amanda; Hardy, Claire; et al.
Highlights: Worldwide, 657 million women are aged 45–59, and around half contribute to the labor force during their menopausal years. The diversity of menopause experience and the effect of menopause on employment are shaped not only by symptoms but also by the physical and psychosocial characteristics of the workplace environment. Menopause is now considered to be an important gender- and age-equality issue, and dealing with its consequences should be part of maintaining an inclusive work environment. Retaining women in employment during their menopausal years will attract, develop and secure a workforce with valuable skills and talent. The EMAS recommendations for employers, managers, healthcare professionals and women aim to make the workplace environment more menopause supportive in the wider context of gender equality and reproductive and post-reproductive health. Abstract: Introduction: Worldwide, there are 657 million women aged 45–59 and around half contribute to the labor force during their menopausal years. There is a diversity of experience of menopause in the workplace. It is shaped not only by menopausal symptoms and context but also by the workplace environment. It affects quality of life, engagement, performance, motivation and relations with employers. Aim: To provide recommendations for employers, managers, healthcare professionals and women to make the workplace environment more menopause supportive, and to improve women's wellbeing and their ability to remain in work. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: Workplace health and wellbeing frameworks and policies should incorporate menopausal health as part of the wider context of gender and age equality and reproductive and post-reproductive health. Workplaces should create an open, inclusive and supportive culture regarding menopause, involving, if available, occupational health professionals and human resource managers working together. Women should not be discriminated against, marginalized or dismissed because of menopausal symptoms. Health and allied health professionals should recognize that, for some women, menopausal symptoms can adversely affect the ability to work, which can lead to reduction of working hours, underemployment or unemployment, and consequently financial insecurity in later life.